DETERMINAN PREFERENSI MENABUNG MAHASISWA DI BANK SYARIAH (STUDI KASUS MAHASISWA PROGRAM STUDI PERBANKAN SYARIAH UMSU) - Cinta Elvina Hassan; Sarwo Edi; Asmaul Husna (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze the influence of Knowledge of Shariah Bank Products, Shariah Bank Services, and Income on students' preference for saving in Shariah Banks. The research method used is quantitative, with a questionnaire as the data collection tool. The questionnaire was analyzed using SPSS 26 software. The research population consists of students in the Sharia Banking study program at the University of Muhammadiyah North Sumatra, with a sample of 30 students selected using quota sampling techniques. Hypotheses were tested using multiple linear regression analysis. The results of this study indicate that preference for saving in Shariah Banks is positively influenced by knowledge of Shariah bank products. However, services and income do not have a significant individual influence, although collectively, all three have a significant influence. This suggests that efforts to increase knowledge about Shariah bank products can enhance the preference for saving in Shariah Banks. Keywords: Shariah Bank Products, Shariah Bank Services, Income, Preference for Saving,